Shape control in surface patterning atop shape memory polymers via indentation, polishing and shape recovery - Prasad, Ayush (2022)
This study aims to analyze the surface pattern created on a shape memory polymer (SMP; thermoset polystyrene) after indentation by a spherical indenter, polishing off the top surface and recovery through the shape memory effect (SME) using the finite element method (FEM) and other computational techniques. Depending on how to polish, three different types of patterns are generated, namely the lens-type protrusion, flat-top protrusion and groove. The actual dimensions of the surface patterns are determined by the polishing depth and the coefficient of friction during indentation. The influence of the latter can be fixed if the coefficient of friction is over a certain value. All the lengths in this study are normalized with the respective indent depth. Hence the results can be scaled. The trends obtained here should be applicable to other shape memory polymers.